USE OF DIGITAL MARKETING INFORMATION TECHNOLOGY IN MARKETING AGRICULTURAL PRODUCTS - Laksamana Khaidir K.N; Muhammad Irwan Padli Nasution (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2024)
This research explores the utilization of information technology, particularly digital marketing, in the marketing of agricultural products. Focusing on Wonotulus Village in Purworejo Regency, Indonesia, the study addresses challenges faced by millennial farmers due to lengthy distribution chains and dependence on middlemen, proposing online marketing strategies as a solution. Through in-depth references and case studies in various villages, the research emphasizes the impact of digital marketing on farmers' bargaining positions, market access, and income growth. The implementation of training, mentoring, and marketplace management activities in different locations demonstrates positive transformations. The results indicate increased enthusiasm, improved knowledge, and successful utilization of social media and e-commerce platforms. The discussion highlights the flexibility required in adapting digital marketing strategies to local characteristics. Challenges such as technology accessibility and varying levels of understanding among farmers are discussed, along with opportunities for global market expansion. Comparative analyses among case studies provide insights into successful aspects and potential improvements. The conclusion underscores the effectiveness of digital marketing, emphasizing the importance of training and mentoring for SME participants. This research contributes to the understanding of how technology can empower farmers, enhance local economic growth, and ensure the sustainability of agricultural businesses.